High Temperature Isothermal and Cyclic Oxidation Behaviour of Pure Recycled Titanium - Monsalve-Gonzalez, A; Artigas-Abuin, A (Emerald Group Holdings Ltd., 2018)
Purpose: This paper aims to analyse the surface evolution of pure recycled titanium subjected to isothermal and cyclic oxidation conditions using dry air as oxidant gas. It is important to mention that the cyclic oxidation behaviour of pure titanium is a process that has been barely studied. Design/methodology/approach: An isothermal and cyclic oxidation reactor was built for these purposes. This installation allows the oxidation of material under the action of any atmosphere and for temperatures up to 1,200°C. For this study, the oxidation behaviour of the material was studied at 850°C and 950°C. Findings: Oxide growth under isothermal oxidation conditions in air follows a parabolic behaviour with an activation energy of 118 kJ/mol, and the oxide phase formed on the surface of the metal was rutile. The cyclic oxidation of the material indicates that oxide is spalled from the surface following linear behaviours; this phenomenon is controlled by the thermal stresses experienced by the samples during heating and cooling cycles. Originality/value: The material is obtained from the production of electrolytic copper, and during its reprocessing practices at high temperature, it was thought that it could experience some abnormal oxidation. In addition, given that pure titanium is currently used for biomedical application, some surface degree can be given by means of oxidation and subsequent spallation process situation that is found during the cyclic oxidation experiments, which could be a low-cost method to engineer a surface for these purposes. © 2018, Emerald Publishing Limited.